Evaluating the effects of high penetrations of roof-top wind turbines on secondary distribution circuits - Kritharas, Petros P.; Ochoa, Luis F. [UNESP]; Papastergiou, Konstantinos D.; Harrison, Gareth P.; IEEE (Ieee, 2006)
Incentives for using wind power and the increasing price of energy might generate in a relatively short time a scenario where low voltage customers opt to install roof-top wind turbines. This paper focuses on evaluating the effects of such situation in terms of energy consumption, loss reduction, reverse power flow and voltage profiles. Various commercially-available roof-top wind turbines are installed in two secondary distribution circuits considering real-life wind speed data and seasonal load demand. Results are presented and discussed.
Keywords: distributed generation; roof-top wind turbines; distribution networks; power flow; fine losses